Solitary Pulmonary Hematoma Radiographically Indistinguishable from Mediastinal Tumor. (24th December 2020) - Komatsu, Teruya; Date, Naoki; Fujinaga, Takuji; Hara, Akira; Kato, Tatsuo
Abstract : Solitary pulmonary hematoma is a rare consequence of blunt chest trauma. Moreover, there has been no reported case of solitary pulmonary hematoma radiographically diagnosed as a posterior mediastinal tumor. We present the case of a 63-year-old man who was referred for an oval-shaped opacity at the left paraspinal area on a chest X-ray. Chest computed tomography showed a well-circumscribed posterior mediastinal tumor on the left paraspinal lesion with extrapleural sign and callus formation on the left ribs posteriorly (7 th to 11 th ribs). The tumor was thoracoscopically confirmed to be a subpleural pulmonary tumor of the left lower lobe, and wedge resection was performed. Histological examination confirmed the diagnosis of pulmonary hematoma. On reviewing the callus formation of the ribs, which was suggestive of rib fractures, the pulmonary hematoma was determined to be traumatic in origin. The postoperative course was uneventful. We reviewed a rare case of pathologically proven traumatic solitary pulmonary hematoma. The rarity of this case is enhanced because the hematoma initially appeared to be a posterior mediastinal tumor.